The influence of different methods of acupuncture on skin surface perfusion - 黄涛 王瑞红 张维波 韩彬 王广军 田宇瑛 张宇沁 (Journal of Traditional Chinese Medicine, 2012)
OBJECTIVE：To compare the effects on the body surface of different kinds of placebo/sham acupuncture with that of traditional needling sensation acupuncture.METHODS：Point Neiguan（PC 6） of 29 healthy subjects,19 males and 10 females,was stimulated with needling sensation,shallow,placebo and deep acupuncture at the non-acupoint.After stimulation with different methods of acupuncture,the change in perfusion of the micrangium in the skin surface around the elbow joint,with Point Quze（PC 3） as its center,was observed with laser Doppler blood-flow imaging.RESULTS：Judging from the absolute value of perfusion of the skin surface micrangium,several methods of acupuncture can cause change in blood flow.The ratio of blood-flow perfusion in the meridian area in and around Quze declined before and after needling insertion in needling sensation acupuncture and shallow acupuncture.This observation did not occur in placebo and non-acupoint acupuncture.Needling sensation acupuncture at an acupoint can relatively reduce the perfusion ofthe micrangium in the projective area of the meridian where the acupoint is located on the body surface（P0.05）,indicating the specificity of meridians.CONCLUSIONS：Stimulation of an acupoint or a point on the body surface with any type of acupuncture can cause change in blood flow in the skin near the needling point.However,the biological mechanism underlying this phenomenon needs to be further explored.